2020
DOI: 10.1016/j.isci.2020.101473
|View full text |Cite
|
Sign up to set email alerts
|

Selective Response to Bacterial Infection by Regulating Siglec-E Expression

Abstract: Summary Interactions between microbes and hosts can be a benign, deleterious, or even fatal, resulting in death of the host, the microbe, or both. Sialic acid-binding immunoglobulin-like lectins (Siglecs) suppress infection responses to sialylated pathogens. However, most pathogens are nonsialylated. Here we determined Siglecs respond to nonsialylated Gram-negative bacteria ( Escherichia coli 25922 and DH5α ) and Gram-positive bacteria ( Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
(131 reference statements)
0
11
0
Order By: Relevance
“…Cells overexpressing Siglec-E with mutated Tyr432 also produced lower amounts of ROS following E.coli infection. This confirmed that Tyr432 in the ITIM domain of Siglec-E is needed for its association with NOX2 subunit p47 phox which promotes ROS production (41). Interestingly, treatment of primary human neutrophils with a synthetic Siglec-9 agonist (pS9L) or anti-Siglec-9 antibody also leads to ROS generation which is inhibited upon SHP-1/2 inhibitor treatment.…”
Section: Siglec-based Modulation Of Ros Productionmentioning
confidence: 55%
See 3 more Smart Citations
“…Cells overexpressing Siglec-E with mutated Tyr432 also produced lower amounts of ROS following E.coli infection. This confirmed that Tyr432 in the ITIM domain of Siglec-E is needed for its association with NOX2 subunit p47 phox which promotes ROS production (41). Interestingly, treatment of primary human neutrophils with a synthetic Siglec-9 agonist (pS9L) or anti-Siglec-9 antibody also leads to ROS generation which is inhibited upon SHP-1/2 inhibitor treatment.…”
Section: Siglec-based Modulation Of Ros Productionmentioning
confidence: 55%
“…Cells overexpressing Siglec-E with mutated Tyr432 also produced lower amounts of ROS following E.coli infection. This confirmed that Tyr432 in the ITIM domain of Siglec-E is needed for its association with NOX2 subunit p47 phox which promotes ROS production ( 41 ).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…The CD24/Siglec-10 signaling pathway protects cancer cells from the immune system, indicating a potential target for cancer immunotherapy (8). Another Siglec, Siglec-E, negatively regulates the inflammatory response in bacterial infection (9,10).…”
Section: Introductionmentioning
confidence: 99%